Towards sweet cherry (Prunus avium L.) breeding: phenotyping evaluation of newly developed hybrids - Ioannis Ganopoulos (2018)
© 2018, Springer Science+Business Media B.V., part of Springer Nature. An increasing demand for cherry production (Prunus avium L.) in Greece led to the development of new high quality sweet cherry cultivars. Self-incompatibility in cherry is one of the most challenging issues for the species’ cultivation and top breeding priority. Τhe present study focuses on the development of new hybrids with improved traits such as productivity, fruit size, organoleptic characteristics and self-compatibility. For this purpose, thirty different cultivars were crossed and produced hybrids that were evaluated according to 34 morpho-physiological characteristics. The results were analyzed using the XLSTAT (version 2014.1) software and a dendrogram was constructed using the agglomerative hierarchical clustering method. Optimal hybrid clustering was achieved when characteristics of great economic importance such as fruit shape and size, growth habit and days to blooming were included in the analysis. Based on the results, new sweet cherry hybrids with the special character of self-compatibility were developed. Our findings provide crucial new information for sweet cherry future breeding programs and cultivation.